Parallel - Colin Campbell (UK Cambridge University Press, 2003)
Max Holland, an assassin for hire, receives a lucrative offer from a mysterious man. But the man's instructions are rather strange and Max isn't sure whether to believe him. It is the start of a job that leads Max to a very unusual place - a world where Max makes a life-changing decision